Pengaruh Perputaran Persediaan, Perputaran Piutang, Perputaran Total Aset, Debt To Equity Ratio Dan Current Ratio Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Periode Tahun 2019-2022 - Sulistriani, Sulistriani; Pranjoto, Gatot Heru (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research was conducted in a quantitative descriptive manner using secondary manner using secondary data obtained on the Indonesia Stock Exchange (IDX). The population of this study is as many as 28 Property and Real Estate Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling method is as many as 10 companies that fit certain criteria. For testing using T test and F. The results of the T test are known that Total Asset Turnover and Debt To Equity Ratio partially have a significant effect on Profitability. While Inventory Turnover, Receivables Turnover and Current Ratio have no effect on Profitability. The results of the F test are known that Inventory Turnover, Receivables Turnover, Total Asset Turnover, Debt To Equity Ratio and Current Ratio simultaneously have a significant effect on Profitability.